Dakwah Digital NiqabSquad dalam Pembentukan Realitas Keagamaan - Regita Cahya Karima; Afif Muhammad; Yeni Huriani (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
This study aims to identify and analyze the form of digital da'wah for veiled women in the form of NiqabSquad social religious reality in the city of Bandung and how women with the NiqabSquad veil construct social-religious reality through digital da'wah in the city of Bandung. The type of research used is qualitative research with a subjective approach, and the research method is descriptive. The data collection techniques used in this study were participatory observation, in-depth interviews and documentation review. The study results show that Da'wah is carried out by the community of veiled women in the NiqabSquad City of Bandung, shaping religious social reality online in WA and IG. In its digital da'wah, this community uses the qawlan balighan, qawlan sadidan, and qawlan layyinan approaches, emphasizing the principles of qawlan layinan, and qawlan sadidan. By prioritizing framing and language selection. The impact of this research can provide a reference for veiled women to create suitable communication activities so that their presence in society can be well received.